A Case Study on Sarcocystis in Laboratory Rabbit - Kaini, D.; Malla, S. (NPI Journal of Science and Technology, 2024)
Sarcocystosis spp. was diagnosed in Newzealand white rabbit which was brought for the purpose of experiment. The rabbit was brought from the local market and rearing in group in cage and feed locally available grasses. No any clinical signs were observed infected rabbit. The physiological along with biochemical and hematological test were performed. At necropsy and tissue harvest, a gross lesion was not observed in heart. During histo-pathological observation, an oval round shape along with longitudinal shape cyst was observed in the myocardium.